Immigrants as Active Citizens: Learning in Social Action - Shibao Guo (Adult Education Research Conference, 2007)
Despite the fact that immigration has played an important role in transforming Canada into an ethno-culturally diverse and economically prosperous nation, immigrants themselves are often criticized as passive citizens. This study attempts to deconstruct this myth by investigating the volunteering experience of Chinese immigrants in Vancouver.